Comparison of Decision Support Systems with DEMATEL-SAW and DEMATEL-TOPSIS in the Process of Journal Acceptance: Case study in The Postgraduate E-Journal of State University of Malang - Amrullah, Ahmad Khakim; Patmanthara, Syaad (Fakultas Teknik Universitas Negeri Malang, 2022)
Concerns about scientific publications have been proliferating in Indonesia. Consequently, the number of published journals in e-journal has been rapidly increasing over the past few years. The growing trend of e-journal hence requires a decision support system in its application. The DSS will help the reviewers in determining the eligibility of an article in the journal’s verification process. Several DSS methods such as DEMATEL, SAW, and TOPSIS, among others, are proposed to provide an effective means in the process. This research aims to present a solid comparison of two combined methods, DEMATEL-SAW and DEMATEL-TOPSIS, as they overcome each method’s shortcomings, in determining the eligibility of an article. The eligibility criteria have been determined as a guide. The calculation results show that the DEMATEL-SAW has a relatively higher degree of accuracy compared to that of DEMATEL-TOPSIS when fewer criteria variables are included, whereas the DEMATEL-TOPSIS method has a higher degree of consistency when being utilized on a variable with more criteria